2018
DOI: 10.4103/0366-6999.243566
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Quick Sequential Organ Failure Assessment Score Combined with Electrocardiography in Risk Stratification of Patients with Acute Pulmonary Embolism

Abstract: Background:The quick Sequential Organ Failure Assessment (qSOFA) score emerged recently. We investigated its contribution to risk stratification in acute pulmonary embolism (PE) by combining with electrocardiography (ECG).Methods:Acute PE patients diagnosed in Beijing Chao-Yang Hospital, Capital Medical University, from 2008 to 2018 were retrospectively studied and divided into high- and low - risk groups by imaging and biomarkers. The ECG scores consisted of tachycardia, McGinn-White sign (S1Q3T3), right bund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The authors concluded that the qSOFA score contributes to the identification of patients with acute PE who are at risk of hemodynamic decompensation and thus require monitoring and possible reperfusion therapy upon ED arrival when used in combination with the ECG score. 20 In our study, the qSOFA score showed worse performance than the NEWS2.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…The authors concluded that the qSOFA score contributes to the identification of patients with acute PE who are at risk of hemodynamic decompensation and thus require monitoring and possible reperfusion therapy upon ED arrival when used in combination with the ECG score. 20 In our study, the qSOFA score showed worse performance than the NEWS2.…”
Section: Discussionmentioning
confidence: 47%
“…19 A 10-year study from China combined the qSOFA score with electrocardiography (ECG) findings to determine the risk stratification in patients with acute PE. 20 The study involved 1318 patients (271 in the high-risk group, 1047 in the low-risk group). The authors established a combination predictive scoring system called the qSOFA-ECG score, which was obtained by adding the qSOFA score and the ECG score.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to ECG indicators (AUC 0.777,95%CI 0.728 ~ 0.827), the q-SOFA score has a high sensitivity, but lower speci city. One study demonstrated that ECG combined with q-SOFA score improved risk strati cation for patients with acute pulmonary embolism [30]. Moreover, several reports indicate that combining heart rate variability with q-SOFA can effectively improve predictive ability for mortality in patients with sepsis [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Such tools include: (a) calculation of Pulmonary Embolism Severity Index (PESI) or simplified PESI (sPESI) scores and the patient's qualification to one of five PESI risk classes or to one of two sPESI classes; (b) ESC classification of pulmonary embolism severity and the risk of early death (low/intermediate-low/intermediate-high/high); (c) determination of blood high-sensitivity troponin I (hs-TNI) or high-sensitivity troponin T (hs-TNT) concentration cut-offs (standard and age-adjusted); (d) assessment for signs of right ventricular (RV) pressure overload in transthoracic echocardiography (TTE) or RV enlargement in CTPA; and, in some cases, (e) determination of blood N-terminal proBtype natriuretic peptide (NT-proBNP) concentration cut-off (mostly ≥ 600 pg/ml) [2,3]. Researchers have also suggested using the following stratifying tools: the presence of coexisting DVT in patients at intermediate-low risk of short-term complications [5]; (b) selected parameters of CTPA imaging [6][7][8], as well as various combinations of the parameters, some of which are mentioned above, such as (i) D-dimer cut-off with sPESI [9], (ii) PESI with NT-proBNP, hs-TNT, and high-sensitivity C-reactive protein cut-offs [10] and (iii) PESI, sPESI and Bova scores with additional patient stratification on the basis of systolic blood pressure [11]; and (c) a combination of a quick Sequential Organ Failure Assessment (qSOFA) score with particular ECG signs [12].…”
Section: Introductionmentioning
confidence: 99%